第64次日本南極地域観測隊におけるペネトレータ観測報告 - 西川, 泰弘; Nishikawa, Yasuhiro; 山本, 耕大; Yamamoto, Kodai; 田中, 智; Tanaka, Satoshi (情報・システム研究機構 国立極地研究所, 2024)
この報告は，第64次南極地域観測隊（JARE-64）において，萌芽研究観測課題の一つである「南極観測用ペネトレータの開発と白瀬氷河および周辺域での集中観測」（課題番号AH1002）により，2022年12月22日から2023年2月11日の夏期間に昭和基地とその周辺の海氷上と南極大陸氷床上で行った試験をまとめたものである．三ヶ年計画の初年度として，第65，66次での観測に必要な基礎データの収集を主目的とし，ペネトレータ（投下型貫入装置）の運用に必要な計測，通信，貫入の3つの要素を5つの試験から評価した． This report summarized the results of the tests and observations conducted by the “Development of Antarctic Observation Penetrators and Intensive Observation in the Shirase Glacier and Surrounding Area” team of the 64th Japanese Antarctic Research Expedition (JARE-64) at Syowa Station on the sea ice and ice sheet from 22nd December 2022 to 11th February 2023. The main purpose of the tests is to collect primary data for JARE 65 and 66th as the first year of the three-year project. We conducted five tests to evaluate the three elements, penetration, measurement, and communication, comprising the penetrator system. departmental bulletin paper